The Effect of Social Media Marketing and Affiliate Marketing on Purchase Intention toward Evolene on Tiktok Shop in Surabaya - Muhamad Fajar Alamsyah Widayanto; Rizky Dermawan (Media Ekonomi dan Manajemen, 2026)
The growing interest in healthy lifestyles and fitness activities has contributed to the expansion of the fitness supplement industry in Indonesia. Despite its strong market position, Evolene experienced a decline in its Top Brand Index ranking in 2026, highlighting the need to evaluate the effectiveness of its digital marketing strategies. This study examines the effects of Social Media Marketing and Affiliate Marketing on consumers' Purchase Intention toward Evolene products on TikTok Shop in Surabaya. A quantitative approach was employed using PLS-SEM with data collected from 120 respondents through purposive sampling. The findings reveal that both Social Media Marketing and Affiliate Marketing positively and significantly influence Purchase Intention, with Affiliate Marketing demonstrating a stronger effect. Relevance of Content emerged as the strongest indicator of Affiliate Marketing, while Trendiness was the strongest indicator of Social Media Marketing. These findings provide theoretical support for the complementary application of the Theory of Planned Behavior (TPB) and Social Cognitive Theory (SCT) in explaining consumers' Purchase Intention within the context of social commerce. The study offers practical insights for optimizing social media content and affiliate marketing strategies to enhance consumers' Purchase Intention.